New drug delivery systems, technological use and repositioning of chloroquine and hydroxychloroquine: An integrative review (Research, Society and Development, 2021)
Chloroquine (CQ) and Hydroxychloroquine (HCQ) have been used historically to treat various conditions that differ from their original medical indication. In addition to their use as antimalarials, these drugs are used to treat autoimmune disorders and have recently gained attention due to in silico and in vitro evidence of their activity against SARS-CoV-2, a fact that has boosted their use rushedly in the treatment of COVID-19. The present study aimed to highlight the advances in research related to the repositioning of CQ and HCQ, their use as adjuvant therapy for treating other pathologies, and the development of new drug delivery systems. A search was performed in PubMed, Science Direct, and Web of Science using the keywords chloroquine, hydroxychloroquine, formulation and repositioning. Articles published in English from 2010 to 2020 that presented CQ or HCQ in the treatment of diseases or as components of formulations and distribution systems were included in the review. We obtained 788 articles, of which 69 were included in the study after screening and refining the search. According to the technological or clinical use of CQ and HCQ, these articles were categorized into four thematic groups: malaria, gene therapy, anticancer therapy, and immune-based diseases. In addition to studies on drug repositioning, we can highlight the articles with proposals for new formulations and drug delivery systems for conditions already treated with such molecules, with a particular focus on overcoming mechanisms of therapeutic resistance.